Intradialytic resistance training for short daily hemodialysis patients as part of the clinical routine: a quasi-experimental study - Baião, Victor M.; Duarte, Marvery P.; Cunha, Vinícius A.; Dourado, Gustavo Í.; Leal, Diogo V.; Viana, João L.; Inda-Filho, Antônio J.; Nóbrega, Otávio T.; Ferreira, Aparecido P.; Ribeiro, Heitor S. (Frontiers in Aging, 2023)
Background and purpose: Hemodialysis patients have chronic systemic inflammation, musculoskeletal impairments, and body composition changes from several factors with increased levels of inflammatory cytokines, catabolic disbalance, and nutritional status which exercise may attenuate. We evaluated the effects of an intradialytic resistance training program on body composition, physical function, and inflammatory markers in patients under short daily hemodialysis treatment. Materials and methods: A quasi-experimental study in clinical routine was conducted over eight months. Measures of physical function (handgrip strength, five-time sit-to-stand, timed-up and go, and gait speed), body composition (by bioelectrical impedance), and inflammatory markers (interleukin [IL]-1 beta, IL-6, IL-8, IL-10, IL-12p70, and tumor necrosis factor-α) were assessed at baseline as well as at four and eight months past continued intervention. Patients underwent two intradialytic resistance training sessions per week supervised by exercise professionals. Results: A total of 18 patients (62 ± 14 years; 55.6% ≥60 years; 44% female) were included. Significant increases in body mass index and basal metabolic rate were found at four and eight months compared to baseline. For physical function, timed-up and go performance improved at four and eight months compared to baseline. The other body composition and physical function measures, as well as all inflammatory markers, did not significantly change over time. Conclusion: A supervised intradialytic resistance training program for patients on short daily hemodialysis treatment, as part of the clinical routine, may induce significant changes in body mass index, basal metabolic rate, and timed-up and go performance.